Student Perceptions of the Basic Concepts of Islamic Education - Wawan Purnama; Tatang Muh Nasir; Mohamad Erihadiana (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research aims to analyze the perceptions of Universitas Pendidikan Indonesia students towards the basic concepts of Islamic education. The method used is a quantitative descriptive method whose data source is students' perceptions of the fundamental concepts of Islamic education. The data was obtained through a questionnaire using Google Forms and distributed to students with a science and technology background. From data processing and analysis, there were no significant differences. Between scientific and technology students' perceptions of the fundamental concepts of Islamic education from a gender perspective, the results of the questionnaire show that there are more positive perceptions from female students than male students. Even though there are differences, both male and female students agree that Islamic education has an essential role in shaping individual character and ethics. Both also agree that the fundamental concepts of Islamic education are relevant in the context of science and technology and can be applied in various scientific disciplines, including science and technology.